Sentidos e significados do educador da infância sobre a família - Alves, Angélica Aparecida Curvelo (2012)
This study aims to understand the senses and meanings constituted by teachers who work in Children Education about children s families and the importance of families-schools relationship for teachers work. Six semi-structured interviews made with teachers from the municipal school network of Suzano-SP, from which only two were analyzed. The selection of the teachers employed the following criteria: they should work exclusively in classes of Children Education; their time in the teaching career should be 15 years or higher; and they should have demonstrated interest in participating in the research after its presentation. The data collected through the interviews were analyzed based on the theoretical framework of the Social historical Psychology, with emphasis on the categories of senses and meaning. The research followed a qualitative approach, and its findings indicated that the participants constituted different senses and meanings about their pupils families and about the importance of family-schools relationship for teachers works, maintaining, however, some common features. Both teachers conceived the participation of families in schools life as important both to improve teaching activities and to understand the configuration of different lifestyles in distinct families arrangements. That information, according to the participants, could help them to explain the children s behavior as well as to customize their way of attending them. The absence of a curriculum in teacher's college, allied to the lack of continuing education showing the centrality of the children's families for teachers work, are seen as hindering the establishment and maintenance of good relationships between schools and its pupils families. These two aspects seem to be fundamental to the construction of a collaborative culture among teachers, administration personnel and pupils families, one, which enables the full development of the children and, consequently, of the new generations